DNA Databanks as a Source of Information about the Criminal Behavior of Individuals Who Have Been Linked to Crimes but Not Identified by Police - Lavergne, Leo (Canadian journal of criminology and criminal justice, 2024)
Perpetrators of offences missing from police files limit the capacity to investigate criminal behaviour for criminological research and operational purposes. Recent studies have shown that forensic DNA databanks, which include samples of DNA not yet matched to an individual, have the potential to address this problem. By examining information associated with criminal cases that involved DNA matches, we demonstrate that individuals who cannot be identified through DNA differ from those for whom such identification is possible. Based on data from 19 years of DNA matches in Quebec, Canada, we were able to assess the co-offending and repeat offending behavior of unidentified and identified individuals as well as the diversification, level of severity, and types of offenses. We found that the crimes of the 1,448 individuals who had not been identified were marginal as compared with those of individuals who had been identified. Unidentified individuals were more likely to act alone in repeated crimes, to be involved in fewer cases, to use less violence, and to become more specialized with increased activity. Our results are consistent with other studies that demonstrate that the criminal activity of unidentified individuals accords with the exposure hypothesis. The association of these findings with a network analysis approach is innovative and could have a greater than expected impact on investigations and policies, as well as having implications for forensic intelligence.